Improving students' mathematics learning outcomes at SMA IT Al-Fityah Pekanbaru through the application of the problem-based learning model - Deny Solihin; Titi Solfitri; Nahor Murani Hutapea (State Islamic University of North Sumatra, 2024)
This research is a class action research that aims to improve the learning process and increase students' mathematics learning outcomes by applying the Problem-Based Learning model in a sequence topic. The subjects of this study were 22 students of class XI IPA SMA IT Al-Fityah Pekanbaru even semester of the 2022/2023 academic year with heterogeneous academic abilities. This study consisted of two cycles with each cycle consisting of four stages, namely planning, acting, observing, and reflecting. The results showed an increase in the mathematics learning outcomes of students in class XI IPA SMA IT Al-Fityah Pekanbaru after participating in learning using the Problem-Based Learning model. The increase in students' mathematics learning outcomes can be seen from the frequency of students who reached the Minimum Achievement Criteria (KKM) increased from cycles I and II respectively 63.63% (14 students) in daily test I to 72,72% (16 students) in daily test II. Thus it can be concluded that the Problem Based Learning model can improve the learning process and improve students' mathematics learning outcomes.